Clinical, biochemical, and genetic characterization of acute hepatic porphyrias in a cohort of Argentine patients - Martinez, María del Carmen (2019)
Background: Acute Hepatic Porphyrias (AHPs) are characterized by an acute neuroabdominal syndrome including both neuropsychiatric symptoms and neurodegenerative changes. Two main hypotheses explain the pathogenesis of nervous system dysfunction: (a) the ROS generation by autooxidation of 5-aminolevulinic acid accumulated in liver and brain; (b) liver heme deficiency and in neural tissues that generate an oxidative status, a component of the neurodegenerative process. Methods: We review results obtained from Acute Intermittent Porphyria (AIP) and Variegate Porphyria (VP) families studied at clinical, biochemical, and molecular level at the CIPYP in Argentina. The relationship between the porphyric attack and oxidative stress was also evaluated in AHP patients and controls, to identify a marker of neurological dysfunction. Results: We studied 116 AIP families and 30 VP families, 609 and 132 individuals, respectively. Genotype/phenotype relation was studied. Oxidative stress parameters and plasma homocysteine levels were measured in 20 healthy volunteers, 22 AIP and 12 VP individuals. Conclusion: No significant difference in oxidative stress parameters and homocysteine levels between the analyzed groups were found.